The economics of biological invasions - Perrings, Charles; Williamson, M. H. (Mark Herbert); Dalmazzone, Silvana; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2000)
The growth of international trade and travel means that more species are being introduced to more places than ever before. This book represents the first concerted effort to understand the economic causes and consequences of biological invasions. The volume discusses the theoretical and methodological issues raised by invasion, including control strategies, modelling options, and a study of the economic, institutional and policy conditions that predispose countries to biological invasions. Also included are case studies of fisheries, agricultural systems, tropical forests and protected areas affected by invasive species in locations such as the Black Sea, Australia and Africa, and an evaluation of control programmes.
pt. 1. Analysis -- pt. 2. Case studies -- pt. 3. Conclusions.
Includes bibliographical references and index.
Keywords: Biological invasions -- Economic aspects; Nonindigenous pests -- Control; Electronic books